The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/codi.15118
|View full text |Cite
|
Sign up to set email alerts
|

A tailored rhomboid mucocutaneous advancement flap to treat anal stenosis

Abstract: Aim Anal stenosis (AS) is a rare but disabling disorder that often represents a complication of anorectal surgery. The aim of our study was to assess the safety and functional outcome of a modified rhomboid flap (MRF) in the treatment of moderate and severe AS. Methods Between January 2002 and September 2017, 50 consecutive patients with moderate and severe AS who underwent an MRF were retrospectively included. Anal continence (Cleveland Clinic Incontinence Score) and symptoms (Obstructed Defaecation Syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 27 publications
2
31
0
1
Order By: Relevance
“…Tailored rhomboid mucocutaneous advancement ap case series of 50 patients by Gallo G et al, reported a success rate of 96% with no recurrence. Bilateral advancement ap was performed for three patients as anal caliber was not satisfactory after the unilateral procedure [7]. Farid et al, had done a prospective study comparing anoplasty measure between house advancement ap, rhomboid, and V-Y anoplasty randomizing the cases with no signi cant difference in caliber of anal canal preoperatively, and has showed highest initial and long term clinical improvement in house advancement ap.…”
Section: Discussionmentioning
confidence: 99%
“…Tailored rhomboid mucocutaneous advancement ap case series of 50 patients by Gallo G et al, reported a success rate of 96% with no recurrence. Bilateral advancement ap was performed for three patients as anal caliber was not satisfactory after the unilateral procedure [7]. Farid et al, had done a prospective study comparing anoplasty measure between house advancement ap, rhomboid, and V-Y anoplasty randomizing the cases with no signi cant difference in caliber of anal canal preoperatively, and has showed highest initial and long term clinical improvement in house advancement ap.…”
Section: Discussionmentioning
confidence: 99%
“…The modified rhomboid flap is demonstrated as a safe and suitable technique for the treatment of moderate and severe AS. Gallo et al reported 0% recurrence rate and 96% success rate in a study with 50 consecutive patients, and significant improvement in the obstructed defecation syndrome scores and the quality of life were observed at 12 months [ 29 ]. The mean anal caliber was found to be 24 mm and significantly different compared to the preoperative measurement.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…He highlighted that no skin sacrifices would have occurred. The operation gained wide popularity in the following decades, which gradually decreased in the 20th century due to the high rate of complications reported, such as anal stenosis, incontinence, or persistent soiling due to mucosal ectropion and deformity (also called “Whitehead's anus”) ( 32 ). In 1924, J. Lockhart-Mummery declared that the death knell of Whitehead operations had been sounded during the London meeting of the American Proctologic Society ( 33 ).…”
Section: Modern Eramentioning
confidence: 99%